Seasonal influence on miRNA expression dynamics of extracellular vesicles in equine follicular fluid - Feugang, Jean M; Gad, Ahmed; Menjivar, Nico G; Ishak, Ghassan M; Gebremedhn, Samuel; Gastal, Melba O; Dlamini, Notsile H; Prochazka, Radek; Gastal, Eduardo L; Tesfaye, Dawit (Journal of animal science and biotechnology, 2024)
BACKGROUND: Ovarian follicular fluid (FF) is a dynamic environment that changes with the seasons, affecting follicle development, ovulation, and oocyte quality. Cells in the follicles release tiny particles called extracellular vesicles (EVs) containing vital regulatory molecules, such as microRNAs (miRNAs). These miRNAs are pivotal in facilitating communication within the follicles through diverse signaling and information transfer forms. EV-coupled miRNA signaling is implicated to be associated with ovarian function, follicle and oocyte growth and response to various environmental insults. Herein, we investigated how seasonal variations directly influence the ovulatory and anovulatory states of ovarian follicles and how are they associated with follicular fluid EV-coupled miRNA dynamics in horses. RESULTS: Ultrasonographic monitoring and follicular fluid aspiration of preovulatory follicles in horses during the anovulatory (spring: non-breeding) and ovulatory (spring, summer, and fall: breeding) seasons and subsequent EV isolation and miRNA profiling identified significant variation in EV-miRNA cargo content. We identified 97 miRNAs with differential expression among the groups and specific clusters of miRNAs involved in the spring transition (miR-149, -200b, -206, -221, -328, and -615) and peak breeding period (including miR-143, -192, -451, -302b, -100, and let-7c). Bioinformatic analyses showed enrichments in various biological functions, e.g., transcription factor activity, transcription and transcription regulation, nucleic acid binding, sequence-specific DNA binding, p53 signaling, and post-translational modifications. Cluster analyses revealed distinct sets of significantly up- and down-regulated miRNAs associated with spring anovulatory (Cluster 1) and summer ovulation-the peak breeding season (Clusters 4 and 6). CONCLUSIONS: The findings from the current study shed light on the dynamics of FF-EV-coupled miRNAs in relation to equine ovulatory and anovulatory seasons, and their roles in understanding the mechanisms involved in seasonal shifts and ovulation during the breeding season warrant further investigation.
Keywords: Ovulation; Seasonal breeding; Extracellular vesicle; Follicular fluid; Pre-ovulation; Mare; Horse; Follicle growth